The validation of oxygen uptake efficiency slope in patients with stroke. Issue 42 (22nd October 2021) - Han, Sheng-Chieh; Fu, Tieh-Cheng; Hsu, Chih-Chin; Huang, Shu-Chun; Lin, Hsin-Yu; Wang, Jong-Shyan
Abstract : Abstract: To evaluate the real aerobic capacity is difficult due to impaired limbs function in stroke patients. Oxygen uptake efficiency slope (OUES) could represent the aerobic capacity in submaximal exercise test. Hence, we designed this observational study to investigate the application of the OUES for evaluating aerobic capacity in these patients. Thirty-seven stroke patients were classified into 2 groups according to their Brunnstrom stage of affected lower limbs. Patients underwent cardiopulmonary exercise testing to assess cardiorespiratory fitness. Minute ventilation and oxygen consumption were measured, and OUES was calculated, compared with healthy reference values, and correlated with the peak oxygen consumption. The predictive validity of submaximal OUES was derived. Study participants' OUES (median 566.2 [IQR, 470.0-711.6]) was 60% of healthy reference values and correlated positively with the peak oxygen consumption ( r = 0.835) ( P < .01). The predictive validity of oxygen uptake efficiency slope at 50% of maximal exercise duration (OUES50 ) and oxygen uptake efficiency slope at 75% of maximal exercise duration (OUES75 ) for oxygen uptake efficiency slope at 100% of maximal exercise duration (OUES100 ) was 0.877 and 0.973, respectively ( P < .01). The OUES50, OUES75, and OUES100 groups were not significantly different; agreement of submaximal and maximal OUES values was strong. OUES is a valuable submaximal index for evaluating cardiorespiratory fitness in stroke patients. Moderate-to-high concurrent validity of this parameter with peak oxygen consumption and the high predictive validity of OUES50 and OUES75 for OUES100 suggest maximal exercise testing in stroke patients who cannot reach maximal exercise is unnecessary.